COMBINED IMMEDIATE PARS PLANA VITRECTOMY AND PHACOEMULSIFICATION AS AN EFFECTIVE TREATMENT ON MACULA-OFF RHEGMATOGENOUS RETINAL DETACHMENT - Hendrawan, Kevin Anggakusuma; Andayani, Ari; Siska, Siska; Umbu Lapu, Ervan Suryanti; Yudistira, Yudistira (International Journal of Retina, 2025)
Introduction: Macula-off rhegmatogenous retinal detachment (RRD) is a complicated condition which can caused poor visual prognosis if not treated properly. Recent studies have been proposed an early surgical treatment on this condition to get better anatomical and functional outcomes. Case Report: A 55-year-old male patient presented with history of blurred vision in left eye of 18 hours duration. Patient had history of seeing flashing light and black dots prior to the symptoms. On evaluation there was a macula-off RRD with immature senile cataract. Immediate phacoemulsification followed by pars plana vitrectomy was done. Good visual recovery with best corrected visual acuity 0.00 logMAR was obtained 3 months after the initial surgery. Discussion: In patient with macula-off RRD, delaying the surgical treatment could possibly worsen the visual prognosis. Accurate diagnosis with timely surgical intervention give a good visual outcome by allowing faster rearrangement of macula anatomy. Conclusion: Early surgical intervention is required to provide better visual outcome on macula-off RRD. In the presents of cataract, combined phacoemulsification with PPV as the main intervention may be considered an appropriate approach. The development of ERM is one of the difficulties that RRD patients face, and it needs to be carefully evaluated to avoid the need for additional surgery.